2021
DOI: 10.2147/jir.s294413
|View full text |Cite|
|
Sign up to set email alerts
|

Natural Dietary Supplement, Carvacrol, Alleviates LPS-Induced Oxidative Stress, Neurodegeneration, and Depressive-Like Behaviors via the Nrf2/HO-1 Pathway

Abstract: Major depressive disorder (MDD) is a debilitating human health condition characterized by mood swings and is associated with a high probability of suicide attempts. Several studies have reported a role of neuroinflammation in MMD, yet the efficacy of natural drug substances on neuroinflammation-associated depression has not been wellinvestigated. The present study examined the neuroprotective effects of carvacrol on lipopolysaccharide (LPS)-induced neuroinflammation, depression, and anxiety-like behavior. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…In the current study, the activation of TRPV4 was caused to the excessive generation of oxidative stress and overload Ca 2+ influx in the SH-SY5Y, BV-2, and HEK293 V4 cells. The modulator role of CARV on several processes such as oxidative stress and Ca 2+ influx in several cells was reported (Chen et al 2015 ; Naeem et al 2021 ). In the current study, the oxidative stress and TRPV4 activation in the SH-SY5Y and HEK293 V4 cells was decreased via the upregulation of GSHPx and GSH, but the downregulation of MDA, cROS, and mROS by the treatment of CARV.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the current study, the activation of TRPV4 was caused to the excessive generation of oxidative stress and overload Ca 2+ influx in the SH-SY5Y, BV-2, and HEK293 V4 cells. The modulator role of CARV on several processes such as oxidative stress and Ca 2+ influx in several cells was reported (Chen et al 2015 ; Naeem et al 2021 ). In the current study, the oxidative stress and TRPV4 activation in the SH-SY5Y and HEK293 V4 cells was decreased via the upregulation of GSHPx and GSH, but the downregulation of MDA, cROS, and mROS by the treatment of CARV.…”
Section: Discussionmentioning
confidence: 94%
“…The decrease of TRPV4 (GSK) and TRPM2 (ADPR and H 2 O 2 ) activators-induced neuronal death in the hippocampus of mice were reported after the administration of antioxidants (Hong et al 2016 ; Kahya et al 2017 ). CARV is a strong antioxidant, and its modulator role on several processes such as free radicals and Ca 2+ influx in several cells was reported (Chen et al 2015 ; Naeem et al 2021 ). At least 11 of 28 subfamilies are activated by oxidative stress (Nazıroğlu et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, previous studies demonstrated the neuroprotective role of Nrf2 not only in laboratory animals but also in human brain samples [30][31][32]. We have previously shown that activation of Nrf2 signaling attenuated infarction area and inflammatory-related pathologies not only in stroke but also in the depression model [33][34][35]. Therefore, Nrf2 may be a suitable therapeutic target for managing epilepsy and seizures.…”
Section: Introductionmentioning
confidence: 99%